2012
DOI: 10.1097/icl.0b013e3182657da5
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Optic Asphericity on Visual Rehabilitation of Corneal Ectasia With a Prosthetic Device

Abstract: Optic asphericity shows promise for optimization of vision in the rehabilitation of corneal ectasia with a prosthetic device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…ScCL also offer very stable platforms for fine adjustment of design to improve visual quality. This was the approach in a recent case report of a keratoconus patient in whom the authors observed a visual improvement related to a decrease in higher order aberrations by adjusting the front surface eccentricity of the lens [44,45]. More sophisticated compensation of higher order aberrations might be possible with contact lenses, although decentration and movement are usually a limitation [46].…”
Section: Vision Improvementmentioning
confidence: 99%
“…ScCL also offer very stable platforms for fine adjustment of design to improve visual quality. This was the approach in a recent case report of a keratoconus patient in whom the authors observed a visual improvement related to a decrease in higher order aberrations by adjusting the front surface eccentricity of the lens [44,45]. More sophisticated compensation of higher order aberrations might be possible with contact lenses, although decentration and movement are usually a limitation [46].…”
Section: Vision Improvementmentioning
confidence: 99%
“… 31 PROSE with 0.6 and 0.8 FSE can improve vision in patients with advanced keratoconus. 14 Hussoin et al have proposed various mechanisms for the role of FSE. FSE may compensate for aberrations from the posterior surface, this may compensate for poor alignment of the optical axis of patient and of the lens, and this eccentricity may restore prolate surface thus improving vision.…”
Section: Manufacturing Of Scleral Lensesmentioning
confidence: 99%
“…FSE may compensate for aberrations from the posterior surface, this may compensate for poor alignment of the optical axis of patient and of the lens, and this eccentricity may restore prolate surface thus improving vision. 14 …”
Section: Manufacturing Of Scleral Lensesmentioning
confidence: 99%
See 2 more Smart Citations